The effect of adding spirulina platensis to the high- protein diet on the tissue increase in the testes of Iraqi lambs - Hamad, Aslam Saud Alwan; Hassan, Shaymaa Ali; Khalid, Nada Aziz (Edelweiss Applied Science and Technology, 2024)
This study was conducted in the animal field - College of Veterinary Medicine / Tikrit University, and lasted for 90 days from 2/10/2022 to 31/12/2022, using two levels of Spirulina platensis (SP), 8 and 12 g/kg of concentrate feed, to raise the value of high protein feed (HP) on the other hand in lamb rations and to investigate the effect of Spirulina supplementation on testicular tissue health and reproductive outcomes in adult lambs through histological examination. 12 local lambs, purchased from Salahuddin markets / Iraq, aged 3 to 4 months, with an average initial weight of 20.5 ± 0.9 kg, were used randomly distributed into 3 treatments / 4 lambs per treatment, as follows: T1 Lamb control group- Lambs were offered the concentrate feed, designated as HP with no Spirulina. T2: Sheep were dosed 8 g Spirulina/ kg concentrate feed. T3: The lambs were supplemented with 12g Spirulina per kg concentrate feed. Light microscopic examination of testes tissues of mature lambs revealed the following differences between sections belonging to the experiment and control groups. There were signs of spermatogenesis in control lambs in the seminiferous tubules with spermatocytes and Sertoli cells, but treated groups presented histopathological alteration as necrosis; amyloid deposit; and spermatogonia degeneration in the interstitial tissue and tunica specials. Indeed, lambs receiving Spirulina experienced different levels of testicular tissue necrosis and amyloid accumulation, which can be considered deleterious effects of the alga. These results indicate that this is possible, therefore more research is necessary to fully determine the impacts of Spirulina supplementation on lamb reproductive health.